Efektivitas Assesment Diagnostik terhadap Hasil Belajar Peserta Didik Kelas 2 SDI Bahrul Ulum - Puji Astuti; Yaya Naufa Khairiyah; Wulida Arina Najwa (STKIP AL HIKMAH SURABAYA, 2023)
Learning with a new paradigm views assessment as no longer limited to reporting student assessments but is seen as a process of collecting and processing information to determine learning needs, development and achievement of learning outcomes. Assessment is an inseparable part of the learning process, one of which is diagnostic assessment. Diagnostic assessment is an assessment activity carried out at the beginning of learning to determine students' initial knowledge. This diagnostic assessment needs to be carried out by educators because students' conditions vary, such as: needs, abilities, experience, level of maturity, and also background. The purpose of diagnostic assessment is to map students based on their abilities so that students can achieve the goals that have been formulated. This research uses a classroom action research method carried out in 2 cycles. Research data was obtained through learning outcomes tests. The research results showed that there was a significant increase in student learning outcomes after implementing the diagnostic assessment. This increase can be seen from the increase in average value and percentage in each cycle.